2017
DOI: 10.1007/s00330-017-4792-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of doxorubicin efficacy in hepatocellular carcinoma by the DNA repair inhibitor DT01 in preclinical models

Abstract: • DT01 combined with TACE leads to significant anti-tumour efficacy without additional toxicity. • A potential anti-angiogenic role of DT01 was identified in preclinical models. • DT01 may potentiate HCC treatment by enhancing the efficacy of TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The GO results indicated that the upregulated DEGs were primarily involved in the ‘daunorubicin metabolic process’ and ‘doxorubicin metabolic process’. Recent studies have demonstrated that daunorubicin interacts with lipid membrane mimetic models of cancer cells in general ( 30 ) and that doxorubicin efficacy is potentiated by the DNA repair inhibitor, DT01 in preclinical animal models of HCC ( 31 ). The enriched GO terms of the downregulated DEGs were primarily involved in ‘acute-phase response’, ‘monooxygenase activity’ and ‘iron ion binding’.…”
Section: Discussionmentioning
confidence: 99%
“…The GO results indicated that the upregulated DEGs were primarily involved in the ‘daunorubicin metabolic process’ and ‘doxorubicin metabolic process’. Recent studies have demonstrated that daunorubicin interacts with lipid membrane mimetic models of cancer cells in general ( 30 ) and that doxorubicin efficacy is potentiated by the DNA repair inhibitor, DT01 in preclinical animal models of HCC ( 31 ). The enriched GO terms of the downregulated DEGs were primarily involved in ‘acute-phase response’, ‘monooxygenase activity’ and ‘iron ion binding’.…”
Section: Discussionmentioning
confidence: 99%
“…The expected benefit of the combination of AsiDNA with CT is based on synergistic effect showed in non-clinical studies. [13][14][15] In a study using NCI-H446 cells, initially sensitive to carboplatin treated with or without AsiDNA, cell populations treated with both carboplatin (2.5 µM) (high dose corresponding to the IC90) and AsiDNA (low dose-2.5 µM) remained very sensitive to the drugs, while carboplatin resistance was observed in all cell populations treated with carboplatin alone after repeated cycles, demonstrating that AsiDNA, at a low sub-active dose, abrogated the emergence of acquired resistance to carboplatin. 15 In fact, by abrogating the DNA repair machinery, AsiDNA sensitises tumours to DNA-damaging agents like CT and RT.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological effect has been confirmed with different routes of administration (intratumoural [IT], intraperitoneal, intravenous [IV], subcutaneous [SC], intra-arterial) and with different treatment modalities: monotherapy, combination with radiotherapy (RT) and other locoregional treatment (i.e., radiofrequency ablation, transcatheter arterial chemoembolisation), various chemotherapy [CT] and PARPi. [13][14][15][16][17] AsiDNA was shown to induce cumulative antitumour activity with low probability of acquired resistance in preclinical models. 18 In the clinic, the drug was first investigated in 23 patients with skin metastases of melanoma in a Phase 1 dose-escalation study, 19 which evaluated the safety and pharmacokinetics (PK) of AsiDNA administered by SC (IT/ peri-tumoural) injections in combination with palliative RT.…”
Section: Introductionmentioning
confidence: 99%
“…Biau et al (2014) conducted a preclinical study in which a cholesterol-conjugated Dbait molecule, DT01, sensitized melanoma cells to radiotherapy both in vitro and in vivo [ 128 ]. In addition, DT01 has been shown to improve the efficacy of the chemotherapeutic doxorubicin in mouse models bearing hepatocellular carcinoma [ 130 ]. Herath et al (2016) investigated the chemosensitizing effects of DT01 in combination with a two-drug chemotherapeutic regimen (oxaliplatin and 5-fluorouracil) in an in vivo colorectal liver metastases model, and have reported significant anti-tumour effects using the combined treatment [ 131 ].…”
Section: Deoxyribonucleic Acid Repair Pathways As Therapeutic Tarmentioning
confidence: 99%